The Association of Unfavorable Traffic Events and Cannabis Usage: A Meta-Analysis - Hostiuc, Sorin; Moldoveanu, Alin; Negoi, Ionuţ; Drima, Eduard (Frontiers in Pharmacology, 2018)
Background. In the last years were published many epidemiological articles aiming to link driving under the influence of cannabis with the risk of various unfavorable traffic events, with sometimes contradictory results. Aim. The primary objective of this study was to analyse whether there is a significant association between druving under the influence of cannabis and unfavorable traffic events. Materials and methods. We used two meta-analytical methods to assess the statistical significance of the effect size: random effects model and inverse variance heterogeneity model. Results. 24 studies were included in the meta-analysis. we obtained significant increases in the effect size for driving under the influence of cannabis tested through blood analysis, with an Odds Ratio (OR) of 1.27 and a Confidence Interval (CI) between 1.36-3.80, death as an outcome, with an OR of 1.56, and a CI between 1.16 and 2.09, and case-control as the type of study, with an OR of 1.99 and a CI between 1.05 and 3.80. Publication bias was very high. Conclusion. Our analysis suggests that the overall effect size for driving under the influence of cannabis on unfavorable traffic events is not statistically significant, but there are significant differences obtained through subgroup analysis. This result might be caused by either methodological flaws (which are often encountered in articles on this topic), the indiscriminate employment of the term “cannabis use” or an actual absence of an adverse effect. When a driver is found, in traffic, with a positive reaction suggesting cannabis use, the result should be corroborated by either objective data regarding marijuana usage (like blood analyses, with clear cut-off values), or a clinical assessment of the impairment, before establishing his/her fitness to drive.